Strategy and human resource management - Boxall, Peter F.; Purcell, John, 1945- (London ; New York : Palgrave Macmillan, 2016)
"How does HRM affect an organisation's chances of survival, its degree of financial success and its reputation in wider society? How is HR strategy shaped within and across organisations, industries and societies, and how can managers improve it to strengthen their organisation's performance? Strategy and Human Resource Management addresses these vital questions. Written by a renowned author team, it treats HR strategy as an essential element in business strategy, whilst integrating a vast range of relevant research and theory. Now in its fourth edition, it continues to challenge academics, students and practitioners to approach HRM from a strategic perspective. New to this edition:[bullet] All chapters have been fully updated, the selection of key studies improved, and the links to major events brought up to date.[bullet] Includes a more thorough analysis of the general principles in strategic HRM.[bullet] It has been restructured to provide a deeper examination of HR strategy in the 'mega contexts' of manufacturing, services, multidivisional firms, and multinationals. This book is an essential companion for upper-level undergraduates, postgraduate students of HRM, and MBA students. Practitioners interested in the role of HRM in successful businesses will also find this a thoroughly engaging and invaluable resource"--
Revised edition of Strategy and human resource management, 2011.
Includes bibliographical references (pages 302-332) and index.
Keywords: Personnel management; Organizational effectiveness; Human capital; BUSINESS & ECONOMICS / General; BUSINESS & ECONOMICS / Human Resources & Personnel Management; BUSINESS & ECONOMICS / Management